Eutheama forrestensis n. sp. (Acotylea, Polycladida, Plathelminthes) from Australia - Bulnes, Veronica N.; Faubel, Anno (Zootaxa, 2003)
A new species, Eutheama forrestensis n. sp., Acotylea, Polycladida, is described from sandy beaches of the eastern coastline of the tropic region of Australia. The species lives both in surface layers and deeper in the sediment down to the coastal groundwater table.